Coexistence of Adjacent Siliciclastic, Carbonate, and Mixed Sedimentary Systems: An Example From Seafloor Morphology in the Northern Lesser Antilles Forearc - Morena, Pierre; Ratzov, Gueorgui; Cattaneo, Antonio; Klingelhoefer, Frauke; Beck, Christian; Seibert, Chloé; Marcaillou, Boris; Feuillet, Nathalie (Frontiers in Earth Science, 2022)
Three main types of factors commonly control the nature of the clasts, the arrangement of the distinctive lithologies, and the general architecture of turbidite systems: sedimentation rate and carbonate production; climates and glacio-eustatism; morphology and tectonics. The coexistence of adjacent systems of distinctive nature is however scarcely documented, and the relative influence of each factor needs better constrain. In the Northern Lesser Antilles Segment (NLAS), carbonate and siliciclastic sediment sources coexist within a 150 km lateral distance, with carbonate platforms lying onto a volcanic substratum, and by a succession of spurs and triangular valleys that are bounded by active normal faulting. To better understand the factors controlling sedimentary processes from the carbonate platforms sources to the deep-sea sinks, we used backscatter, bathymetry, multichannel seismic and sub-bottom profiles. Sedimentary systems are dominated by siliciclastic input (by retrogressive erosion of confined canyons affecting the volcanic slope), carbonate input (by carbonate sediment transported by oceanic- and wind- driven submarine currents beyond the leeward edges of carbonates platforms) or both. In the mixed systems, the retrogressive erosion of the canyon head determine the nature of the source (volcanic on the slope, carbonate when the canyons reach the shelf-edge). Glacio-eustatism has a key role on carbonate availability on the platform, as attested by the presence of drowned platforms. The main contribution of this study is the identification of the major role that tectonic activity plays in the short-distance coexistence of the distinctive sedimentary systems, since fault-bounded V-shaped valleys offer alternating leeward and windward edges favoring carbonate- or mixed-systems. Additionally, the steep slope gradient induced by normal faults and regional subsidence seems to be the main factor controlling sediment dispersal. It causes multiple line sources, and the dispersion of gravity-driven currents under the effect of hydraulic jumps, thus preventing the formation of a channelized system. Our study provides a modern analogue of adjacent systems dominated by distinctive lithologies in a tectonically active area. The results appear particularly appropriate to decipher the nature of ancient source-to-sink systems dominated by complex tectonics, paleo-bathymetry and sediment routings.